Nefrolitiasis: Una revisión actualizada - Herrera Muñoz, Alvaro Adolfo (2020)
Kidney stones are solid accumulations of different mineral salts incorporated into an organic matrix, which originate in the kidney or upper urinary tract. There are different types according to their main component, with calcium being the most prevalent. The incidence is higher in middle-aged men, which also have a higher risk of recurrence. Among the most important risk factors are alterations in the urinary concentration of minerals, metabolic syndrome and low water consumption. The most frequent clinical manifestations are pain, hematuria and bacteriuria; however, the majority of cases are asymptomatic. The gold  standard for diagnosis is computerized axial tomography (CAT) scan without contrast. Regarding treatment, it includes the pharmacological approach with nonsteroidal anti-inflammatory (NSAIDs) drugs and surgical management according to the type of kidney stone. Two of the most important complications are acute renal failure and chronic kidney disease, which cause significant morbidity and mortality; making prevention through proper hydration, low sodium and reduced animal protein intake and a normal calcium level diet vital for clinical management.